2015
DOI: 10.1017/s0021859615000453
|View full text |Cite
|
Sign up to set email alerts
|

Response of grapevine phenology to recent temperature change and variability in the wine-producing area of Sremski Karlovci, Serbia

Abstract: The historical temperature and phenological data were analysed for the region of Sremski Karlovci, one of the oldest grapevine growing areas in Europe, with the aim of detecting trends of changes in the data, evaluating the sensitivity of grapevine phenology to temperature and revealing diversity among cultivars in their response to observed changes in temperature. The onset dates of four major phenological stages (budburst, flowering, veraison and harvest), along with the corresponding growth intervals betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 60 publications
6
38
1
1
Order By: Relevance
“…Evidence for differences between cultivars in their rate of advancement was also observed by Petrie and Sadras () who showed apparent ‘environment‐by‐cultivar interactions', although these were not quantified in the same way as in this study. These differences between cultivars found here also support the work by Ruml et al () who showed, in a long term study (1986–2011) in Serbia, that different cultivars had different degrees of advancement for harvest [harvest in their study, however, was defined as stage 89 ‘berries ripe for harvest’ on the BBCH scale (Lorenz et al ) which, as already discussed, is a subjective decision, in contrast to the DOYM metric, used in this study].…”
Section: Discussionsupporting
confidence: 89%
“…Evidence for differences between cultivars in their rate of advancement was also observed by Petrie and Sadras () who showed apparent ‘environment‐by‐cultivar interactions', although these were not quantified in the same way as in this study. These differences between cultivars found here also support the work by Ruml et al () who showed, in a long term study (1986–2011) in Serbia, that different cultivars had different degrees of advancement for harvest [harvest in their study, however, was defined as stage 89 ‘berries ripe for harvest’ on the BBCH scale (Lorenz et al ) which, as already discussed, is a subjective decision, in contrast to the DOYM metric, used in this study].…”
Section: Discussionsupporting
confidence: 89%
“…Thermal requirements expressed in various forms of heat accumulation or degree-day indices have also been considered to help describe and predict grapevine phenology in different viticultural areas (Parker et al, 2011;Fila et al, 2014;Hall et al, 2016;and others). In some research, measures of maximum and average temperatures were found to be more important than minimum temperatures in describing phenology timing (Bock et al, 2011;Ruml et al, 2016). However, Urhausen et al (2011) indicated the need to use a combination of climate variables to best describe events such as budbreak (BB), where heat accumulation in March, maximum temperatures in April, and frost days during January-March were the best predictors.…”
Section: Changes In Vine Development Related To Temperature and Precimentioning
confidence: 99%
“…They may also modify the limits of winegrowing regions, such as those of Denomination of Origin (MORIONDO et al, 2013). With regard to grapevine phenology, they may change the dates of budbreak, flowering, veraison, maturity and leaf fall (VINK et al, 2012;CABRÉ et al, 2016;HALL et al, 2016;RUML et al, 2016).…”
Section: Introductionmentioning
confidence: 99%